Reliable workflow for inversion of seismic receiver function and surface wave dispersion data: a “13 BB Star” case study - Kajetan Chrapkiewicz; Monika Wilde-Piórko; Marcin Polkowski; Marek Grad (Journal of Seismology, 2020)
Non-linear inverse problems arising in seismology are usually addressed either by linearization or by Monte Carlo methods. Neither approach is flawless. The former needs an accurate starting model; the latter is computationally intensive. Both require careful tuning of inversion parameters. An additional challenge is posed by joint inversion of data of different sensitivities and noise levels such as receiver functions and surface wave dispersion curves. We propose a generic workflow that combines advantages of both methods by endowing the linearized approach with an ensemble of homogeneous starting models. It successfully addresses several fundamental issues inherent in a wide range of inverse problems, such as trapping by local minima, exploitation of a priori knowledge, choice of a model depth, proper weighting of data sets characterized by different uncertainties, and credibility of final models. Some of them are tackled with the aid of novel 1D checkerboard tests—an intuitive and feasible addition to the resolution matrix. We applied our workflow to study the south-western margin of the East European Craton. Rayleigh wave phase velocity dispersion and P-wave receiver function data were gathered in the passive seismic experiment “13 BB Star” (2013–2016) in the area of the crust recognized by previous borehole and refraction surveys. Final models of S-wave velocity down to 300 km depth beneath the array are characterized by proximity in the parameter space and very good data fit. The maximum value in the mantle is higher by 0.1–0.2 km/s than reported for other cratons.

Thermal properties of the crust and the lithosphere–asthenosphere boundary in the area of Poland from the heat flow variability and seismic data - Jacek Majorowicz; Marcin Polkowski; Marek Grad (International Journal of Earth Sciences, 2019)

Verification of the seismic P-wave velocities under Moho boundary: Central Poland case study, LUMP profile - Monika Dec; Marcin Polkowski; Tomasz Janik; Krystyna Stec; Marek Grad (Acta Geophysica, 2019)

The geophysical characteristic of the lower lithosphere and asthenosphere in the marginal zone of the East European Craton - Marek Grad; Jacek Puziewicz; Jacek Majorowicz; Kajetan Chrapkiewicz; Simone Lepore; Marcin Polkowski; Monika Wilde-Piórko (International Journal of Earth Sciences, 2018)

Crustal and uppermost mantle S-wave velocity below the East European Craton in northern Poland from the inversion of ambient-noise records - Simone Lepore; Marcin Polkowski; Marek Grad (International Journal of Earth Sciences, 2018)

Local Seismic Events in the Area of Poland Based on Data from the PASSEQ 2006–2008 Experiment - Marcin Polkowski; Beata Plesiewicz; Jan Wiszniowski; Monika Wilde-Piórko (Acta Geophysica, 2016)

Seismic basement in Poland - Marek Grad; Marcin Polkowski (International Journal of Earth Sciences, 2016)

Seismic Wave Velocities in Deep Sediments in Poland: Borehole and Refraction Data Compilation - Marcin Polkowski; Marek Grad (Acta Geophysica, 2015)

Passive Seismic Experiment “13 BB Star” in the Margin of the East European Craton, Northern Poland - Marek Grad; Marcin Polkowski; Monika Wilde-Piorko; Jerzy Suchcicki; Tadeusz Arant (Acta Geophysica, 2015)

Seismic wave velocities in the sedimentary cover of Poland: Borehole data compilation - Marek Grad; Marcin Polkowski (Acta Geophysica, 2012)